Site characterization and foundation design for the emplacement of radio telescope antennas at the Matjiesfontein Space Geodesy Observatory - Janse van Rensburg, Cornelius Johannes Theodorus (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.